Evaluation of hypoglycemic properties and fertility effect of Piper sarmantosum Roxb. aqueous leaf extract in streptozotocin induced diabetic mice - Ampa - Luangpirom; Watchara Kourchampa; Pichet Somsapt (International Journal of Phytomedicine, 2014)
Male mice of ICR strain (6-7 week old, 30-40 g) were used for evaluation of the hypoglycemic and fertility effect of Piper sarmentosum Roxb. leaf extract. Diabetes was induced by intraperitoneal (i.p) injection of streptozotocin (STZ) (6.0 mg/100gBW) and glibenclamide (reference drug) 1 mg/ 100gBW and Piper sarmentosum Roxb. leaf extract (PS) at 60 and 100 mg/100gBW were orally administered (per os) for 21 days. The hypoglycemic activity of PS was 73.04 and 120.96% of the glibenclamide. Meanwhile, the blood insulin level also significantly increased by 8.25 and 50.53 % of the diabetic control. The concordant results showed that diabetic pancreatic islets were impaired and improved after extract treatment. However, the fertility status test showed that the seminal quality and blood testosterone of diabetic mice decreased significantly (P< 0.05) as compared to the normal mice and significantly increased when compared to the diabetic control after long-term treatment. In conclusion, Piper sarmentosum Roxb. aqueous leaf extract at doses of 60 and 100 mg/100 gBW revealed hyperglycemic properties in diabetic mice. They also improved both pancreatic islet function and fertility status of diabetic mice after 21 days of extract treatment.